Antagonistic activity of selected marine-derived streptomyces spp. against plesiomonas shigelloides / Angelyn Melaya Kloni - Kloni, Angelyn Melaya (2010)
In this study, primary and secondary screenings were conducted to evaluate the antibacterial and anti-yeast potential of the eleven selected marine-derived Streptomyces spp., particularly against P. shigelloides. The strains were categorized into three colour groups for morphological grouping according to the colour of aerial mycelium; namely grey, yellow green, and white colour groups. Diffusible pigments were produced by eight of the strains tested. Strain(s) from grey and white with red diffusible pigments colour groups displayed strong antibacterial activity. The yeasts tested were resistant to the bioactive metabolite(s) produced by some of the Streptomyces spp. which had shown high activity against the bacteria tested. In primary screening, there was no inhibition of growth of yeasts tested; C. albicans and C. parasilopsis. Of the streptomycete strains tested, eight strains were active against at least one bacteria tested. In secondary screening, four strains inhibited all the yeasts tested. Meanwhile, all strains were active against at least one bacteria tested. Streptomyces strain T15 displayed the best antibacterial activity against B. subtilis, P. aeruginosa, and P. shigelloides. Of the streptomycetes tested, three strains were found to display strong inhibition against at least one pathogen tested in both primary and secondary screenings. Meanwhile, two and three strains displayed moderate inhibition against at least one pathogen tested in primary and secondary screenings, respectively. Furthermore, six and all the strains displayed weak inhibition against at least one pathogen tested in primary and secondary screenings, respectively. The antibacterial and anti-yeast activities were prominent in secondary screening, where five of the strains exhibited broad spectrum activity.Streptomyces strain T15 was selected for further studies. Culture conditions(media and agitation or static) were optimised to enhance the production of bioactive metabolite(s) in submerged fermentation. It was noted that fermentation of strain T15 in ISP2 medium at an incubation period of nine days at 28ºC ± 2ºC, pH 6.10 ± 1.70, and shaking at a speed of 120 rpm was the most ideal for growth and bioactive metabolite(s) production antagonistic to P. shigelloides at laboratory conditions. During the twelve days fermentation, the highest bioactive metabolite(s) production of strain T15 was noted on day nine in all the fermentation media used in this study. The highest bioactive metabolite(s) production by nine-day old strain T15 was achieved in ISP2 medium; however, the bioactive metabolite(s) production started on day six. The nature of culture condition that is, either agitation or static had an effect on the production of bioactive metabolite(s). For agitation culture condition, ISP2 medium was considered as the best fermentation medium for strain T15 based on the higher production of bioactive metabolite(s) that it supported compared to SA medium. Meanwhile, for static culture condition, ISP4 medium was the only fermentation medium that supported the bioactive metabolite(s) production by strain T15.